A novel mutation in the XPA gene results in two truncated protein variants and leads to a severe XP/neurological symptoms phenotype. (13th November 2014) - Lehmann, J.; Schubert, S.; Schäfer, A.; Laspe, P.; Haenssle, H.A.; Ohlenbusch, A.; Gratchev, A.; Emmert, S.
Abstract: Background: The nucleotide excision repair (NER) pathway repairs UV‐induced DNA lesions in an accurate fashion and prevents UV‐irradiated areas of the skin from tumour formation. The XPA protein plays a major role in DNA damage demarcation as well as stabilization of other NER factors and was found to be defective in xeroderma pigmentosum (XP) complementation group A patients. Objective: Characterization of four new XP‐A patients. Methods: Genomic and cDNA sequencing, post‐UV cell survival of living cells, host‐cell reactivation of patients' fibroblasts and Western blotting. Results: One of the four investigated patients shows a novel mutation leading to two different truncated protein variants. Three patients contain the already described p.R228X mutation. All patient cell lines exhibit a strong UVC sensitivity and reduced NER capability. In most of the cases stable protein expression was detected. Conclusion: We discovered four new XP‐A patients and a novel XPA mutation resulting in two diverse patient alleles.